Macular relocation after photodynamic therapy for recurrent choroidal neovascular membrane: visual results and histopathological findings. Issue 8 (24th July 2003) - Stanga, P; Hiscott, P; Li, K; Wong, D
Abstract : Background/aims: The findings in a patient treated with photodynamic therapy (PDT) followed by macular relocation surgery (MRS) are presented. Methods: Histopathological evaluation of the choroidal neovascular membrane (CNV) specimen including immunohistochemical assessment. Results: Microscopy revealed one CNV area that was richly vascular with attached retinal pigment epithelial cell monolayer and another area that was made up of densely collagenous avascular tissue with adherent fragments of Bruch's membrane and glial elements. Conclusion: The findings suggest that the PDT treated part of the CNV may have been adherent to the neuroretina and may have contributed to the formation of the macular hole. Caution is advised when considering MRS for CNV previously treated PDT.